Analysis The Impact Of Industrial Areas On HIV Aids Incidence - Masruroh Masruroh; Bernadeta Verawati; Heny Noor Wijayanti (Journal of Midwifery, 2022)
Research Background : South Jepara Regency is an industrial area that absorbs a lot of labor around the company's establishment. Over time, the incidence of HIV AIDS has increased. Data from the Jepara health office in Pecangaan District in 2018 reached 48 cases, in Mayong District in 2018 it reached 29 cases and in Kalimatan District in 2018 it reached 21 cases.Research Objective: To analyze the impact of industrial estates on the incidence of HIV AIDS.Research Methods: This type of research is qualitative with in-depth interview data collection techniques. Time of data collection in November 2019. The research location is Pecangaan, Kalinyamatan and Mayong Districts, Jepara Regency, Central Java. The number of research informants is 10 people. Miles and Huberman interactive data analysisThe results of the study: the positive impact of increasing economic welfare and reducing the number of unemployed, while the negative impact of water pollution, the proliferation of hangouts and the construction of many boarding houses.Conclusion: Industrial growth in the southern part of Jepara Regency, has positive and negative impacts. Industrial environmental conditions as an indirect cause of the increasing incidence of HIV AIDS.